Production of vitamin B2 (riboflavin) by Bacillus subtilis. Issue 8 (5th January 2022) - Chu, Ronghao; Li, Rui; Wang, Chen; Ban, Rui
Abstract: Riboflavin is one of the main micronutrients required for the human body for cellular respiration. It is the precursor of flavin mononucleotide and flavin adenine dinucleotide coenzymes crucial for the production of energy. The development of biotechnology has given rise to microbial procedures that strongly compete with the chemical synthesis approach and hence the fermentation process of riboflavin by microorganisms was initiated. Therefore, the main aim of this review is to investigate the production of riboflavin by Bacillus subtilis fermentation. The introduction of the microbial synthesis method has found that regulatory and structural genes involved in the synthesis of vitamin B2 are overexpressed, which has eventually enhanced the strain productivity and production of the vitamin via industrial fermentation. Using B. subtilis to synthesize riboflavin can reduce the production cost and increase the yield of riboflavin. The emergence of microbial synthesis methods has effectively increased the yield of riboflavin, and the study of the process of riboflavin synthesis by B. subtilis is of great significance for improving production, reducing costs and using renewable raw materials. © 2021 Society of Chemical Industry (SCI).